RANCANGAN SISTEM INFORMASI PENGOLAHAN DATA BARANG DAN ALAT-ALAT INSTALASI LISTRIK PADA CV. ANGKASA VENUS JAMBI - Irma Suana; Defi Oktiana Putri (JURNAL AKADEMIKA)
CV. Space Venus Jambi is a private company which is located directly under the auspices of AKLI (Electrical and Mechanical Contractors Association of Indonesia), on the CV. Space Venus Jambi the data processing is still using simple way is by using the Microsoft Excel application program alone, the problems that arise during information is generated on the sale of data processing is less accurate and frequent errors. The research concludes that the resulting information after processing sales data using Microsoft Visual Basic 6.0 and mySQL databases can be better because the error rate is getting lower over the data entered is correct as well as a database created must also be true.